2021
DOI: 10.1371/journal.pone.0246954
|View full text |Cite
|
Sign up to set email alerts
|

Does birth weight affect neonatal body weight, growth, and physiology in an animal model?

Abstract: Infant birth weight affects neuromotor and biomechanical swallowing performance in infant pig models. Preterm infants are generally born low birth weight and suffer from delayed development and neuromotor deficits. These deficits include critical life skills such as swallowing and breathing. It is unclear whether these neuromotor and biomechanical deficits are a result of low birth weight or preterm birth. In this study we ask: are preterm infants simply low birth weight infants or do preterm infants differ fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Birthweight (i.e., mass) across the sample ranged from 0.42 to 1.7 kg. Birthweights were significantly smaller in preterm infants than in full‐term infants (Mann–Whitney U test; p = 0.001; preterm trueX¯ = 0.84 kg, full‐term trueX¯ = 1.43 kg) (see also Adjerid et al, 2021; Andersen et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Birthweight (i.e., mass) across the sample ranged from 0.42 to 1.7 kg. Birthweights were significantly smaller in preterm infants than in full‐term infants (Mann–Whitney U test; p = 0.001; preterm trueX¯ = 0.84 kg, full‐term trueX¯ = 1.43 kg) (see also Adjerid et al, 2021; Andersen et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
“…However, birthweight had very little effect on bone strength in the infant pig sample overall. Previous studies have found that birthweight per se is also a poor predictor of functional deficits during pig development (i.e., swallowing performance; Adjerid et al, 2021). Again, it may be that accelerated intrauterine development buffers infant pigs—and perhaps other precocial infants—against the deficits predicated by low birthweight in more altricial species.…”
Section: Resultsmentioning
confidence: 98%
“…At 7 days of age (roughly equivalent to 1–2 months postnatal in humans [Eiby et al, 2013 ]), infant pigs were recorded bottle feeding barium contrast enhanced milk replacer formula. Recordings were made using videofluoroscopy with a high‐speed camera at 100 frames per second (XC1M digital camera; Xcitex) in the lateral view (GE 9400C‐Arm, 75–85kV, 5 mA) following established feeding protocols (Adjerid et al, 2021 ; German et al, 2004 ; Mayerl, Myrla et al, 2020 ). During each recording session, piglets were bottle‐fed, first on the intermediate training nipple, then were allowed approximately 20 swallows on each of the four nipple types in randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…Infant mammals have highly developed oral sensory abilities at birth, which provides specific input to the central nervous system for efficient and effective suckling. When the sensory connections involved in infant feeding are disrupted, feeding performance is compromised and infants may suffer from illness, malnourishment, and potentially life‐long developmental issues (Adjerid et al, 2021 ; Ballester et al, 2018 ; Catchpole et al, 2020 ; DeLozier et al, 2018 ; Ding et al, 2013 ; Gould et al, 2015 , 2016 , 2017 , 2020 ; Hadders‐Algra, 2018 ; Liu et al, 2018 ; Mayerl, Catchpole, et al, 2020 ; Zimmels et al, 2021 ). Yet, sensory motor integration in human infant suckling is not fully understood, making it difficult to predict how changes to sensory input affect feeding behaviors (Gould et al, 2019 ; Jean, 2001 ; Young et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation